Navigating the Complexities of Cellular Therapy Patents: Regulatory Challenges, Ethical Implications, and Global Trends - Raymond R Tjandrawinata; Henry Soelistyo Budi (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
New ways of therapeutic methods have now altered modern medicine. Modern cellular therapies, from stem cell and CAR-T therapies to CRISPR-based gene editing therapy, provide new ways to tackle difficult-to-treat diseases. These breakthrough therapies bring a complex web of regulatory, ethical, and legal challenges. These are also in relation to intellectual property. The patenting of such therapies raises a multitude of unresolved questions ranging from the challenges of balancing innovation with access and ensuring equity while incentivizing research to navigating the complex global patent systems. This article aims to investigate the diverse regulatory frameworks for patenting cellular therapy in major jurisdictions. Discussions on ethical concerns regarding the modification of human cells and seeks to balance innovation with access to life-saving treatments will be done at great length. This paper will also provide insight into the potential evolution of the global patent system to address the distinctive challenges posed by cellular therapies. Key cases and providing forward-thinking recommendations will also be discussed.